Penyuluhan Hukum Di Kecamatan Mojogedang Kabupaten Karanganyar Dalam Rangka Meningkatkan Mutu Hukum Melalui Sosialisasi Bantuan Hukum - Marisa Kurnianingsih; Rokhman Adi Putera Nugraha; Aristya Windiana Pamuncak (Masyarakat Berdaya dan Inovasi, 2021)
Legal aid is legal services provided by legal aid providers free of charge to legal aid recipients. Based on the basic constitution of the Indonesian nation which aims to guarantee the constitutional rights of everyone to get recognition, guarantee, protection, and legal certainty that is just and equal treatment before the law as a means of protecting human rights, where this is one form of protecting community rights and the form of the state in being responsible for providing legal aid for the poor as a manifestation of access to justice. The purpose of the legal counseling activity is to provide skills as well as an understanding of legal aid and how to obtain it for the community in Mojogedang Village, Mojogedang District, Karanganyar Regency. The method used in this activity is socialization which is then followed by legal assistance for the community in Mojogedang Village, Mojogedang District, Karanganyar Regency.